Gender effects and sexual-orientation impact on androstadienone-evoked behavior and neural processing - Krajnik, Jacqueline; Kollndorfer, Kathrin; Nenning, Karl-Heinz; Lundström, Johan N.; Schöpf, Veronika (Frontiers in Neuroscience, 2014)
In humans, the most established and investigated substance acting as a chemosignal, i.e., a substance that is excreted from the body, is 4,16-androstadien-3-one (AND). AND, which is found in sweat and saliva, is known to be responsible for influencing several variables, such as psychophysiological status, behavior, as well as cortical processing. The aim of the present review is to give insight into the variety of AND effects, with special regard to specific cross-sexual characteristics of this putative human chemosignal, emphasizing the neural activation patterns and factors such as contextual conditions. This review highlights the importance of including those contributing factors into the analysis of behavioral as well as brain-related studies.